SISTEM INFORMASI PENERIMAAN MAHASISWA BARU STMIK WIDYA UTAMA BERBASIS WEB MENGGUNAKAN PAYMENT GATEWAY - Purbasari, Wika; Setianti, Novita; Sunaryono, Sunaryono (Politeknik Harapan Bersama, 2023)
STMIK Widya Utama's new students in 2021 reached 482 out of a total of 789 registrants. New student admission activities include the registration process, file collection, and reporting process. In paying the registration fee, most of the prospective new students in making payment transactions still use conventional or manual methods. In addition, the process of collecting personal data and file requirements is still not systemized. The process is still offline using Google Forms, so many find data constraints such as duplicate, invalid, or unfilled data. Stacked physical files take a long time to look up data. Web-Based New Student Admission Information System Using Waterfall Method with the stages of Analysis, Design, Implementation, and Testing. Testing using the ISO 9126 standard. The instrument used is a questionnaire for testing aspects of functionality and usability and an instrument is a tool for testing reliability and efficiency. The result of this research is web-based new student admission information system using the Payment Gateway. Testing on the functionality aspect resulted in a value of 100% (satisfactory) and on the usability aspect resulted in a vlue of 91,4% (satisfactory), besides that, testing on the reliability aspect resulted in a value of 100% (satisfactory) and the efficiency test resulted in a value of 83% for performance and 78% for structure and time for page request is 0,9 second (satisfactory). With the result of this tests, it can be concluded that the web-based new student admission information system using the payment gateway can be a solution to backup an activity of new student admission in STMIK Widya Utama.Key Words âˆ’ Information System; New College Student Admission; Payment Gateway;STMIK Widya Utama's new students in 2021 reached 482 out of a total of 789 registrants. New student admission activities include the registration process, file collection, and reporting process. In paying the registration fee, most of the prospective new students in making payment transactions still use conventional or manual methods. In addition, the process of collecting personal data and file requirements is still not systemized. The process is still offline using Google Forms, so many find data constraints such as duplicate, invalid, or unfilled data. Stacked physical files take a long time to look up data. Web-Based New Student Admission Information System Using Waterfall Method with the stages of Analysis, Design, Implementation, and Testing. Testing using the ISO 9126 standard. The instrument used is a questionnaire for testing aspects of functionality and usability and an instrument is a tool for testing reliability and efficiency. The result of this research is web-based new student admission information system using the Payment Gateway. Testing on the functionality aspect resulted in a value of 100% (satisfactory) and on the usability aspect resulted in a vlue of 91,4% (satisfactory), besides that, testing on the reliability aspect resulted in a value of 100% (satisfactory) and the efficiency test resulted in a value of 83% for performance and 78% for structure and time for page request is 0,9 second (satisfactory). With the result of this tests, it can be concluded that the web-based new student admission information system using the payment gateway can be a solution to backup an activity of new student admission in STMIK Widya Utama.Key Words âˆ’ Information System; New College Student Admission; Payment Gateway;